Consolidation state of incoming sediments to the Nankai Trough subduction zone: Implications for sediment deformation and properties. (14th July 2014) - Kitajima, Hiroko; Saffer, Demian M.
Abstract The hydromechanical properties of accreted and underthrust sediments are key parameters controlling the mechanics of earthquakes and the development of fluid pressure in subduction zones. We conducted consolidation tests on sediments from the Philippine Sea Plate (PSP) in the Nankai Trough to understand the consolidation state and hydraulic properties of the incoming sediment section before its incorporation into the subduction zone. We used mudstone and sandstone cores sampled from the Integrated Ocean Drilling Program Nankai Trough Seismogenic Zone Experiment at two reference sites (Site C0011 located on a basement low; and Site C0012 located on a basement high). Our experimental results indicate that most of the mudstone samples are normally consolidated or overconsolidated, with overconsolidation ratios (OCR) ranging from 0.89 to 2.52 at Site C0011 and 0.86 to 3.85 at Site C0012. Higher OCR values at Site C0012, at least at shallow depths, are likely caused by erosional unloading. This implies that Site C0011 may serve as a better geotechnical reference site. We also find that mudstones accreted along the frontal thrust are severely overconsolidated relative to coeval mudstones at Site C0011, which likely reflects enhanced consolidation due to increased horizontal tectonic stress. Sandstones in the incoming section on the PSP exhibit 2–3 orders of magnitude higher in situ permeability than the mudstones, and the siliciclastic sandstone we tested maintains a high permeability at stresses up to at least 70 MPa, suggesting that the sandstones may act as important pathways for drainage or pore pressure translation from depths of several kilometers.